Protocolo para la inspección, mantenimiento y evaluación de alcantarillas en Costa Rica - Sojo-Quesada, Mauricio Antonio (Instituto Tecnológico de Costa Rica, 2016)
The increased of the flow rates, the lack of urban planning and some unclear guidelines for the maintenance of road assets, have caused the partial or total collapse of drainage structures, for which the Government of Costa Rica has had to make tough decisions to avoid further troubles, which have caused significant structural damage to the roads, resulting millions in losses to users and entrepreneurs. The objective of this research is to perform a protocol for inspection, maintenance and evaluation of sewers that are on the roads of Costa Rica. To do that, different types of sewers and their environment were identified, surveys were applied to people working in companies and institutions that provide maintenance to structures, in order to identify the main problems they face in their daily basis. Based in the information collected from guidelines and recommendations in international standards, several proposals were given for the standardization of procedures and techniques as guidelines and technical guidelines specifications to help the people in charge of the maintenance and inspection, implement in the most effective and correct way to execute the maintenance of sewers in Costa Rica. All information gained from the implementation of the protocol, the public and private institutions can plan correctly the maintenance and replacement of sewers, as well as maximize the resources invested in each of the structures.
Proyecto de Graduación (Maestría en Ingeniería Vial) Instituto Técnologico de Costa Rica, Escuela de Ingeniería en Construcción, 2016
Keywords: Alcantarillas; Cuenca; Bombeo; Eflorescencia; Barreras de contención